Congenital anomalies of the urethra - M. I Katibov (Vestnik Urologii, 2021)
Congenital anomalies of the urethra are insufficiently covered in the literature, except for hypospadias and epispadias. Therefore, there is a significant gap in information on the diagnosis, classification and management of patients with such anomalies among practising physicians and researchers. Also, the urgency of studying this problem is due to the complexity of these malformations. This fact dictates the need for a very careful and correct approach to timely surgical treatment and subsequent rehabilitation, which will minimize the negative medical and social consequences of these anomalies. Taking these circumstances into account, key data on the most common congenital anomalies of the urethra were summarized in the form of a lecture material based on modern scientific advances. The following malformations of the urethra are considered as the main options: hypospadias; epispadias; urethral valves, obliterations, strictures, diverticula and cysts; Guerin's sinus; hypertrophy of verumontanum; agenesis of the urethra; urethral duplication; megalourethra; urethral fistulas; urethral polyp. Moreover, all types of anomalies are presented with illustrations of real clinical examples. The information from this study can be successfully used in the daily work for practising physicians of various profiles, scientific and pedagogical activities when teaching students at medical universities, residency training, postgraduate studies and in the courses of advanced training and professional retraining, as well as in conducting scientific research in this direction.